Information graphics - Rendgen, Sandra; Holmes, Nigel, 1942-; Rogers, Simon; Wurman, Richard Saul, 1935 (Taschen, 2012)
"Our everyday lives are filled with a massive flow of information that we must interpret in order to understand the world we live in. Considering this complex variety of data floating around us, sometimes the best -- or even only -- way to communicate is visually. This unique book presents a fascinating perspective on the subject, highlighting the work of the masters of the profession who have created a number of breakthroughs that have changed the way we communicate. Information Graphics has been conceived and designed not just for graphics professionals, but for anyone interested in the history and practice of communicating visually. The in-depth introductory section, illustrated with over 60 images (each accompanied by an explanatory caption), features essays by Sandra Rendgen, Paolo Ciuccarelli, Richard Saul Wurman, and Simon Rogers; looking back all the way to primitive cave paintings as a means of communication, this introductory section gives readers an excellent overview of the subject. The second part of the book is entirely dedicated to contemporary works by today's most renowned professionals, presenting 200 graphics projects, with over 400 examples -- each with a fact sheet and an explanation of methods and objectives -- divided into chapters by the subjects Location, Time, Category, and Hierarchy."--Publisher description
Keywords: Communication; Graphic arts; Information visualization; Visual communication